(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Chronic Kidney disease(CKD) is an important cause of morbidity worldwide, and the prevalence is increasing. Hypertension, diabetes, obesity and age are amongst the most important risk factors. AIMS & OBJECTIVE: To study the socio-demographic and clinical factors in the patients of CKD, and to find which is the most frequent factor associated with CKD. Study Design: This is a cross sectional study. Setting: The 4 medical units and the nephrology ward of Jinnah Hospital, Lahore along with the nephrology outpatient department. Duration of Study: April to May 2016. Sample Size:80 patients. Type of Sampling: Non-random purposive sampling Results: the frequency of hypertensives in the CKD patients was 68.3%,diabetes was present in 46%, 56% of the population was male, 53% had a history of using traditional alternative medicine (Specifically Hakeem Medications). The mean age of the population was 44.3+ 16.5. Conclusions: Hypertension is the most frequent risk factor found in the CKD patients. However, its control is not upto the mark. Strategies should be employed to control hypertension and diabetes to prevent further progression of disease in this country where there are insufficient medical services.